Extensive genic and allelic heterogeneity underlying inherited retinal dystrophies in Mexican patients molecularly analyzed by next‐generation sequencing - Zenteno, Juan C.; García‐Montaño, Leopoldo A.; Cruz‐Aguilar, Marisa; Ronquillo, Josué; Rodas‐Serrano, Agustín; Aguilar‐Castul, Luis; Matsui, Rodrigo; Vencedor‐Meraz, Carlos I.; Arce‐González, Rocío; Graue‐Wiechers, Federico; Gutiérrez‐Paz, Mario; Urrea‐Victoria, Tatiana; et al. (Molecular genetics & genomic medicine, 2020)
Background Retinal dystrophies (RDs) are one of the most genetically heterogeneous monogenic disorders with ~270 associated loci identified by early 2019. The recent application of next‐generation sequencing (NGS) has greatly improved the molecular diagnosis of RD patients. Genetic characterization of RD cohorts from different ethnic groups is justified, as it would improve the knowledge of molecular basis of the disease. Here, we present the results of genetic analysis in a large cohort of 143 unrelated Mexican subjects with a variety of RDs. Methods A targeted NGS approach covering 199 RD genes was employed for molecular screening of 143 unrelated patients. In addition to probands, 258 relatives were genotyped by Sanger sequencing for familial segregation of pathogenic variants. Results A solving rate of 66% (95/143) was achieved, with evidence of extensive loci (44 genes) and allelic (110 pathogenic variants) heterogeneity. Forty‐eight percent of the identified pathogenic variants were novel while ABCA4, CRB1, USH2A, and RPE65 carried the greatest number of alterations. Novel deleterious variants in IDH3B and ARL6 were identified, supporting their involvement in RD. Familial segregation of causal variants allowed the recognition of 124 autosomal or X‐linked carriers. Conclusion Our results illustrate the utility of NGS for genetic diagnosis of RDs of different populations for a better knowledge of the mutational landscape associated with the disease. Extensive genic an allelic heterogeneity in retinal dystrophies in Mexican patients was identified. Genotyping of large cohorts of RD patiets from different ethnic groups is warranted for a better molecular knowledge of retinal degeneration.